Pengaruh Pelayanan Fiskus dan Penerapan E-Filing Terhadap Kepatuhan Wajib Pajak Badan - Rubenson Lumbantobing; Jonnardi; Henny (Fakultas Ekonomi Universitas Tarumanagara, 2023)
This study examines the effect of tax services and the implementation of E-Filing on corporate taxpayer compliance. The sample comes from companies listed in KPP Pratama Jakarta Kebon Jeruk Satu as a sampling frame. Based on purposive sampling, 105 questionnaires were distributed, exceeding the specified number of samples, which was 90 questionnaires. The hypothesis is carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) 3.0. The results of this study indicate that the tax service and the application of E-Filing have a positive effect on taxpayer compliance. The Directorate General of Taxes is expected to improve service quality so that taxpayers are enthusiastic in carrying out their tax obligations.